Assessing self-forgiveness through the Enright Self-Forgiveness Inventory in the Spanish population: a validation study - Molinero, Clara; Kasprzak, Agata; Bonete, Saray; Gallo-Giunzioni, Karla (Frontiers in Psychology, 2023)
Introduction Self-forgiveness has been a complex construct to define, which has resulted in a shortage of instruments that adequately measure it as a process. In Spain, until now there is only one validated instrument to measure self-forgiveness, for this reason the present study aims to validate the Enright Self-Forgiveness Inventory (ESFI). Method A sample of 276 people (84 men, 192 women) aged from 18 to 25 years, completed the Enright Self-Forgiveness Inventory (ESFI) after its adaptation to Spanish, as well as the Enright Forgiveness Inventory-30 (EFI-30), the Narcissistic Personality Inventory (NPI), the Short form of Social Desirability Scale (M-C SDS), the Scale of psychological wellbeing (RYFF) and the Depression, Anxiety and Stress Scale-21 (DASS-21). Results The Confirmatory Factor Analysis showed a good fit for the original six-factors structure (CFI = 0.93, TLI = 0.92, RMSEA = 0.063). The results showed good psychometric qualities (both validity and reliability) and association between self-forgiveness and social desirability, depression, anxiety, narcissistic traits, and purpose in life as expected theoretically. Discussion The ESFI-30 shows good psychometric properties within the Spanish context and is an appropriate instrument for evaluating self-forgiveness for research and clinical intervention.